2011
DOI: 10.1111/j.1365-2672.2011.04991.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the prevalent microbiota of human male and female forehead skin compared to forearm skin and the influence of make-up

Abstract: Aims:  To compare the bacterial diversity of two different ecological regions including human forehead, human forearm and to estimate the influence of make‐up. Methods and Results:  Twenty‐two swab‐scraped skin samples were analysed by profiling bacterial 16S rRNA genes using PCR‐based sequencing of randomly selected clones. Of the 1056 clones analysed, 67 genera and 133 species‐level operational taxonomic units (SLOTUs) belonging to eight phyla were identified. A core set of bacterial taxa was found in all sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 30 publications
3
76
0
4
Order By: Relevance
“…Subject sex, handedness, and time since last hand washing also appear to affect bacterial community composition (Fierer et al 2008). A subsequent study confirmed the differences in community composition between sexes when investigating the forearm, but found little influence of sex on forehead community composition, thereby supporting early observations of variability among anatomical regions (Staudinger et al 2011).…”
Section: Dawning Of the Molecular Microbiology Eramentioning
confidence: 62%
“…Subject sex, handedness, and time since last hand washing also appear to affect bacterial community composition (Fierer et al 2008). A subsequent study confirmed the differences in community composition between sexes when investigating the forearm, but found little influence of sex on forehead community composition, thereby supporting early observations of variability among anatomical regions (Staudinger et al 2011).…”
Section: Dawning Of the Molecular Microbiology Eramentioning
confidence: 62%
“…Sex-specific differences previously have been observed in the bacterial biota of human hand surfaces (Staudinger et al, 2011), the forearm (Fierer et al, 2008), the gut (Mueller et al, 2006;Li et al, 2008) and the subgingival crevice (Slots et al, 1990;Schenkein et al, 1993;Umeda et al, 1998;Kumar 2013). Oral bacteria have been observed to change with periods of major hormonal fluctuations, such as puberty or pregnancy, and the hormonal changes may have a causative role in this observation of diversion of microorganisms by sex (Kumar, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Viruses have the potential to eradicate certain cellular hosts or to provide them with beneficial gene functions such as beta lactamases ( Figure 1); thus, human oral viruses may help to shape the natural history of oral microbiome membership. The sex specificity we identified in oral viruses suggests that viral communities respond to the same potentially hormone-driven signals that govern the sex specificity also found in bacterial communities on the skin (Fierer et al, 2008;Staudinger et al, 2011), gut (Mueller et al, 2006;Li et al, 2008) and the oral cavity (Slots et al, 1990;Umeda et al, 1998). Understanding the impact of environment and genetics on human microbiota may be critical to the evaluation of disease processes such as chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The stratum corneum (SC), the outer layer of the epidermis, is the most exposed organ of the human body and is composed of molecules derived from our own skin cells, our microbiota, and the environment (1). In addition, it may be possible that personal hygiene products, the clothing we wear, and the food we eat can affect the chemical composition of the skin (2,3).…”
mentioning
confidence: 99%